GSK-3β inhibits autophagy and enhances radiosensitivity in non-small cell lung cancer - Jialin Ren; Tingting Liu; Yang Han; Qiongzi Wang; Yanzhi Chen; Guang Li; Lihong Jiang (BMC, 2018)
Abstract Background Radiotherapy is one of the most common and effective treatment methods for cancer, and improving the radiosensitivity of tumor tissues during the treatment process is vital. We report the mechanisms of glycogen synthase kinase 3 (GSK-3) β-regulated autophagy and the effects of autophagy on radiosensitivity in non-small cell lung cancer (NSCLC). Method Immunohistochemical staining was performed to determine GSK-3β tissue expression in 89 NSCLC patients with follow-up data and the expression status of GSK-3β and autophagy in NSCLC tissues after X-ray radiotherapy. Western blots were used to quantitate changes in autophagy-related protein expression after A549 cells were treated with GSK-3β inhibitors and after H460 cells were transfected with GSK-3β mutants with different activities and X-ray irradiated. Clonogenic assays were used to measure the effect of autophagy on cellular proliferation. Results GSK-3β expression positively correlated with NSCLC differentiation (P < 0.05), and GSK-3β negativity was associated with a better prognosis in 89 NSCLC patients. After X-ray irradiation, the expression levels of GSK-3β and p62 were decreased in NSCLC tissues, and the expression levels of the autophagy-related protein LC3 were increased. A549 and H460 cells were selected as representative GSK-3β-high and GSK-3β-low expression cell lines. After transfecting H460 cells with different GSK-3β mutants [wild type GSK-3β (GSK-3β-WT), constitutively active GSK-3β (GSK-3β-S9A), and catalytically inactive GSK-3β (GSK-3β-K85R)] and subjecting these cells to X-ray irradiation, AMPK and LC3 expression levels decreased, and p62 expression levels increased. These effects were particularly significant for the GSK-3β-S9A mutant. In A549 cells, after GSK-3β inhibition and X-ray irradiation, AMPK and LC3 protein expression levels increased. Moreover, when autophagy was inhibited, cell proliferation decreased. Conclusion Our studies revealed that GSK-3β expression is associated with NSCLC differentiation, and patients with GSK-3β-negative tumors had a better prognosis. X-ray irradiation inhibited GSK-3β expression and promoted autophagy. Therefore, GSK-3β inhibits autophagy and enhances the radiosensitivity of NSCLC cells.